Impact of lipid emulsions in parenteral nutrition on platelets: a literature review - Betul Kisioglu; Funda Tamer (Journal of Nutritional Science, 2024)
Lipid emulsions are essential components of parenteral nutrition solutions that provide energy and essential fatty acids. The complexity of the formulations of lipid emulsions may lead to adverse outcomes such as platelet reactivity and changes in platelet aggregation and related coagulation. Platelets are responsible for haemostasis; they activate and demonstrate morphological changes upon extracellular factors to maintain blood fluidity and vascular integrity. Although parenteral nutrition lipid emulsions are generally found safe with regard to modulation of platelet activity, studies are still accumulating. Thus, this review aims to investigate platelet-related changes by parenteral nutrition lipid emulsions in human studies. Studies have pointed out patients at risk of bleeding and increased platelet aggregation responses due to the administration of lipid emulsions. Lipid emulsions may further benefit patients at high risk of thrombosis due to anti-thrombotic effects and should be cautiously used in patients with thrombocytopenia. The reported platelet-related changes might be associated with the fatty acid change in the plasma membranes of platelets following changes in platelet synthesis and plasma levels of eicosanoids. In conclusion, studies investigating platelets and parenteral nutrition should be supported to minimize the adverse effects and to benefit from the potential protective effects of parenteral nutrition lipid emulsions.